Thermotolerance effect of plant growth-promoting Bacillus cereus SA1 on soybean during heat stress - Khan, Muhammad Aaqil; Asaf, Sajjad; Khan, Abdul Latif; Jan, Rahmatullah; Kang, Sang-Mo; Kim, Kyung-Min; Lee, In-Jung (BMC microbiology, 2020)
Incidences of heat stress due to the changing global climate can negatively affect the growth and yield of temperature-sensitive crops such as soybean variety, Pungsannamul. Increased temperatures decrease crop productivity by affecting biochemical, physiological, molecular, and morphological factors either individually or in combination with other abiotic stresses. The application of plant growth-promoting endophytic bacteria (PGPEB) offers an ecofriendly approach for improving agriculture crop production and counteracting the negative effects of heat stress. We isolated, screened and identified thermotolerant B. cereus SA1 as a bacterium that could produce biologically active metabolites, such as gibberellin, indole-3-acetic acid, and organic acids. SA1 inoculation improved the biomass, chlorophyll content, and chlorophyll fluorescence of soybean plants under normal and heat stress conditions for 5 and 10 days. Heat stress increased abscisic acid (ABA) and reduced salicylic acid (SA); however, SA1 inoculation markedly reduced ABA and increased SA. Antioxidant analysis results showed that SA1 increased the ascorbic acid peroxidase, superoxide dismutase, and glutathione contents in soybean plants. In addition, heat stress markedly decreased amino acid contents; however, they were increased with SA1 inoculation. Heat stress for 5 days increased heat shock protein (HSP) expression, and a decrease in GmHSP expression was observed after 10 days; however, SA1 inoculation augmented the heat stress response and increased HSP expression. The stress-responsive GmLAX3 and GmAKT2 were overexpressed in SA1-inoculated plants and may be associated with decreased reactive oxygen species generation, altered auxin and ABA stimuli, and enhanced potassium gradients, which are critical in plants under heat stress. The current findings suggest that B. cereus SA1 could be used as a thermotolerant bacterium for the mitigation of heat stress damage in soybean plants and could be commercialized as a biofertilizer only in case found non-pathogenic.